2022
DOI: 10.3390/foods11172629
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Attitude towards Sustainability in Italy: Process of Validation of a Duly Designed Questionnaire

Abstract: This study aimed to describe the process of validation of a questionnaire assessing Italian consumers’ perception of food sustainability. The study has a multiphase design. Phase 1 consisted in translating and structuring the questionnaire. Phase 2 aimed at assessing the validity of the content by experts. Phase 3 consisted of a pilot study (n = 150) carried out to revise the questionnaire based on the reactions of consumers representing the target group of the assessment. The questionnaire showed adequate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Regarding nutrition knowledge, the total score obtained by the apprentice chefs was in line with the results reported for the sample of university students with a nutrition background enrolled by Rosi et al [23] to validate the questionnaire applied in this study. Considering the Italian adult population, Aureli and colleagues recently validated a 12-item questionnaire [40], but in this example, the instrument aimed at investigating the attitudes of individuals, without specifically investigating their actual knowledge. Some studies on the topic of nutrition and food sustainability knowledge are reported in the literature; however, comparisons are difficult due to the peculiarities of the study design and target population of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding nutrition knowledge, the total score obtained by the apprentice chefs was in line with the results reported for the sample of university students with a nutrition background enrolled by Rosi et al [23] to validate the questionnaire applied in this study. Considering the Italian adult population, Aureli and colleagues recently validated a 12-item questionnaire [40], but in this example, the instrument aimed at investigating the attitudes of individuals, without specifically investigating their actual knowledge. Some studies on the topic of nutrition and food sustainability knowledge are reported in the literature; however, comparisons are difficult due to the peculiarities of the study design and target population of our study.…”
Section: Discussionmentioning
confidence: 99%
“…There are still limitations to this approach. In the IDGs, the sustainability recommendations were developed without an evaluation of Italian consumers’ considerations of sustainability [ 44 ]. As reported by Rossi et al, 2022 [ 18 ], the sustainability of diet is an aspect that is still not completely exploited, in which the risk of bias and “personal” interpretation is also possible, given the limited sources of information, based on consensus documents.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation to the development of the sustainability of diet in the IDGs, was related to the fact that the commission included nutrition experts with an under-representation of environmental sustainability competencies. In a modern approach, nutritional recommendations should consider the environmental implications of food choice, and the development of nutritional recommendations are tasks for community nutrition specialists and public health experts [ 44 ]. A multidisciplinary approach to the development of nutritional recommendations is important for the wide range of aspects belonging to different disciplines that should be considered together in order to identify possible solutions for the transition towards a healthy and sustainable diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations